Study on the Optimal Design of Hydraulic Wedge Brake based on the Simulated Annealing Algorithm - Sun Haibo (Jixie chuandong)
In order to solve the problems of large design margin and high manufacturing cost of traditional heavy duty vehicle drum brake,the new type hydraulic wedge type brake is regarded as research subjects,the calculation formulas of wedge brake torque,brake drum surface average temperature,maximum temperature are got,the design of the model is optimized through the simulated annealing algorithm,finally,the optimization model is validated through the finite element calculation and experiment. The results show that the stress value of hydraulic wedge brake after the optimization of the key components can meet the material requirement of use,the hydraulic wedge brake after the optimization in different brake pressure and initial speed of braking conditions braking efficiency is with high stability.